(untitled) (Strathmore Law Journal, 2021)
Does the increase in Chinese foreign direct investment (FDI) inflows into Kenya portend doom for human rights in the country? The prominent narrative has been that FDI undermines human rights in host states, especially those in the developing world. This narrative is countered by claims that there exists a mutually affirming relationship between FDI and human rights. Proponents of this view posit that FDI facilitates the diffusion of human rights norms and correlates with the improved rule of law in host states. They also point to emerging human rights jurisprudence in international investment arbitration as evidence of a reciprocal relationship between FDI and human rights. In light of these arguments, this paper analyses the extent to which such a reciprocal relationship bears out between Chinese FDI and human rights in Kenya. It will be demonstrated that given the lack of a framework for human rights accountability for corporations at the international level, the restrictive treatment of human rights in international investment arbitration tribunals and weak institutional capacity in host states, a positive overlap between FDI and human rights is hardly a panacea for human rights protection in Kenya. Therefore, a synergy of legal measures and non-legal measures provide a pragmatic approach to insulate human rights from violations that may be associated with Chinese FDIs.